Curriculum for Children with Special Needs at Aisyiyah Bustanul Athfal Kindergarten: Kurikulum Anak Berkebutuhan Khusus di TK Aisyiyah Bustanul Athfal - Pangesti, Vida; Salim, Agus (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Inclusive education has gained global attention as an effort to ensure equal learning opportunities for all children, including those with special needs. Specific background: However, many non-inclusive schools remain unprepared to provide appropriate services, particularly in fulfilling curriculum needs for children with special needs at the kindergarten level. Knowledge gap: Limited studies explicitly explore how non-inclusive early childhood institutions address curriculum adaptation for children with special needs. Aims: This study aims to examine the implementation of learning curricula for children with special needs in a non-inclusive kindergarten and to identify the challenges faced by the institution. Results: Findings reveal that while the school accepts children with special needs, it lacks a specific curriculum, adequate facilities, and trained human resources, relying instead on partial adjustments to regular curricula and basic individualized support. Novelty: This study contributes insight into how non-inclusive schools attempt to accommodate children with special needs despite structural limitations. Implications: The results highlight the urgent need for policy support, teacher training, and curriculum design tailored to early childhood special needs education. Highlights: Curriculum adaptation in non-inclusive kindergartens. Lack of trained teachers and resources. Need for policy and practical support. Keywords: Early Childhood Education, Special Needs, Inclusive Curriculum, Non-Inclusive Schools, Educational Policy